2023
DOI: 10.3390/toxics11090737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Silymarin Extract as a Potent Antioxidant Supplement in Diazinon-Exposed Rainbow Trout: Oxidative Stress and Biochemical Parameter Analysis

Mahdi Banaee,
Federica Impellitteri,
Cristiana Roberta Multisanti
et al.

Abstract: This study aimed to investigate the effects of diazinon on fish, focusing on hepatotoxic biomarkers and the potential protective effects of silymarin supplementation. One hundred eighty rainbow trout were randomly assigned to four groups: control, diazinon exposed (0.1 mg L−1), silymarin supplemented (400 mg kg−1), and diazinon + silymarin. Blood samples and liver tissue were collected after 7, 14, and 21 days of exposure to analyze biochemical parameters and oxidative biomarkers. Diazinon exposure in fish res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In summary, this discussion provides a systematic exploration of ALT activity variations across fish organs in response to naphthalene exposure. Research conducted by 36 , 37 has reported a decrease in ALT activity in the liver and an increase in plasma ALT activity, 38 have also noted decreased ALT levels, potentially due to hepatocyte damage and insufficiencies in various organs. These findings emphasize the sensitivity of ALT activity to environmental contaminants and its crucial role in fish metabolism and health.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, this discussion provides a systematic exploration of ALT activity variations across fish organs in response to naphthalene exposure. Research conducted by 36 , 37 has reported a decrease in ALT activity in the liver and an increase in plasma ALT activity, 38 have also noted decreased ALT levels, potentially due to hepatocyte damage and insufficiencies in various organs. These findings emphasize the sensitivity of ALT activity to environmental contaminants and its crucial role in fish metabolism and health.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the modulatory effect of silymarin on other fish species has been documented. A decline in ALP activity was reported in striped catfish ( Pangasianodon hypophthalmus) fed with silymarin supplemented diet [ 28 ], zebra cichlid ( Cichlasoma nigrofasciatum ) exposed to malathion [ 5 ], and rainbow trout ( Oncorhynchus mykiss ) specimens exposed to diazinon [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide exploration of the modulatory role of antioxidants found within phytochemicals, as a means to diminish free radical-induced damage, underscores the growing significance of this area of research [ 13 ]. In this context, recognised as “milk thistle” is Silybum marianum , a member of the Asteraceae family, which holds a significant status as a herb with remarkable antioxidant properties [ 28 , 29 ]. Silymarin is often used as a dietary supplement for liver-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of diazinon and its metabolites in fish can lead to various effects, including oxidative stress [ 26 , 27 ], alterations in hematological parameters [ 28 ], endocrine imbalances [ 18 ], and hyperactivity [ 29 ]. Numerous studies [ 30 33 ] have demonstrated that diazinon possesses the capacity to elicit profound transformations in liver enzymes and the corresponding biochemical indices. Consequently, the evaluation of fish health following exposure to acute or chronic diazinon toxicity can be performed by determining the activity of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), total antioxidant (T-AOC), cortisol, as well as immune parameters including lysozyme, IgM, and complement component C3.…”
Section: Introductionmentioning
confidence: 99%